Influential opinion leaders - Jakub Steiner; Colin Stewart (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
We present a simple model of elections in which experts with special interests endorse candidates and endorsements are observed by the voters. We show that the equilibrium election outcome is biased towards the experts' interests even though voters know the distribution of expert interests and account for it when evaluating endorsements. Expert in uence is fully decentralized in the sense that individual experts have no incentive to exert influence. The effect arises when some agents prefer, ceteris paribus, to support the winning candidate and when experts are much better informed about the state of the world than are voters.
Keywords: C72; D83; D72; 330; election; manipulation; global game